Integrasi Kearifan Lokal dalam Pembelajaran IPS di SD Untuk Membentuk Karakter Cinta Budaya - Aulia, Nurul Dinda; Pratiwi, Anisa; Nuri, Annisa Yulia; Rahmah, Rahmah; Nasution, Amanda Malika; Yusnaldi, Eka (Education Achievement: Journal of Science and Research, 2025)
This study aims to examine the importance of integrating local wisdom into Social Studies (IPS) education at the elementary school level as one of the efforts to build a culture-loving character in students. Local wisdom, which encompasses cultural values, traditions, and local knowledge, has great potential to enrich the learning material and strengthen the nation's cultural identity. Through various strategies, such as the use of local wisdom-based learning media, project-based approaches, and the development of contextual learning resources, IPS education can connect theory with students' everyday life practices. This integration not only helps students understand social, economic, and cultural concepts more deeply but also fosters pride and love for their own culture. Although there are some challenges in its implementation, such as teachers' limited understanding and a lack of resources, efforts to integrate local wisdom can be achieved through collaboration between teachers, communities, and cultural experts. Thus, teaching based on local wisdom will support the strengthening of the nation's character, grounded in the noble values of Indonesian culture.